Breaking the cycle of infertility with clomiphene citrate and letrozole for successful ovulation induction for obese women with PCOS - Permadi, IGN Wiranta; Prasetyaji, IMN Wiranta (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Polycystic ovarian syndrome (PCOS) is a hyperandrogenous state with oligo-anovulation. Letrozole is more efficient than CC in promoting ovulation and facilitating pregnancy in women with PCOS who are overweight or obese.   ABSTRACT Objective: Indonesia has a higher prevalence of PCOS, a common endocrine disorder that affects 4% to 8% of women who are of reproductive age. Obesity, insulin resistance, and anovulatory infertility are all linked to PCOS. The ability of letrozole and clomiphene citrate (CC) to induce ovulation in overweight or obese PCOS patients was examined in this meta-analysis. Materials and Methods: PRISMA criteria were followed when conducting a systematic literature search utilizing PubMed, Google Scholar, Cochrane Library, and ScienceDirect. Keywords included PCOS, obesity, clomiphene, and letrozole. Studies published between 2000 and 2024 in English, with full-text accessibility, were included. The search yielded 260 studies, of which nine were selected for quantitative synthesis. Results: Letrozole showed a 12% increase in ovulation and a 33% increase in pregnancy rates compared to clomiphene citrate (CC). There was no discernible difference in the two groups' endometrial thickness. This meta-analysis finds that letrozole is more successful than CC in triggering ovulation and achieving conception in overweight or obese PCOS patients. Conclusion: In women with PCOS who are overweight or obese, letrozole works better than clomiphene citrate (CC) to induce ovulation. Because it is accessible and reasonably priced, CC is still the first-line treatment, even if its efficacy is lesser. As a second-line therapy, letrozole is advised for women who are resistant to or do not react to CC.